A method based on infrared detection for determining the moisture content of ceramic plaster materials. (September 2015) - Macias-Melo, E.V.; Aguilar-Castro, K.M.; Alvarez-Lemus, M.A.; Flores-Prieto, J.J.
Abstract: In this work, we describe a methodology for developing a mathematical model based on infrared (IR) detection to determine the moisture content ( M ) in solid samples. For this purpose,  an experimental setup was designed, developed and calibrated against the gravimetric method. The experimental arrangement allowed for the simultaneous measurement of M and the electromotive force ( EMF), fitting the experimental variables as much as possible. These variables were correlated by a mathematical model, and the obtained correlation was M = 1.12 × exp ( 3.47 × E M F ), ±2.54%. This finding suggests that it is feasible to measure the moisture content when it has greater values than 2.54%. The proposed methodology could be used for different conditions of temperature, relative humidity and drying rates to evaluate the influence of these variables on the amount of energy received by the IR detector. Highlights: A methodology to determine moisture content by IR radiation is proposed. Moisture content and the radiation emitted are measured simultaneously. Moisture content decreases as the radiation emitted diminishes. The proposed methodology can be potentially applied for similar samples.